Moderating effects of organizational culture on the relationship between emotional intelligence, work motivation and work commitment - Irfan, Saira (2018)
Literature has established that multiple forms of work commitment exist and employees may be committed to more than one form of commitment. Hence, organizational commitment alone cannot adequately explain employees’ work commitment. Although numerous scholars have established a link between emotional intelligence, work motivation, and organizational commitment in a variety of work sectors, yet, there is a paucity of research which investigates these variables with work commitment as well as organizational culture in unison. Thus, the purpose of this research was to examine the relationship between organizational culture, emotional intelligence, work motivation, and work commitment of university academic staff in Pakistan. The study also measured the moderating effects of organizational culture and its types (clan, adhocracy, hierarchy and market) on the relationship between emotional intelligence, work motivation, and work commitment. In addition, differences in emotional intelligence, work motivation and work commitment were also analyzed based on demographic variables. Three hundred and fifty-one academic staff, selected through simple random sampling technique from nine public universities in the state of Punjab, Pakistan, participated in the study. Cross-sectional design was employed, and the data was collected using standardized validated questionnaires. The hypothesized model was tested using Partial Least Squares (PLS) approach. The analysis revealed that organizational culture, emotional intelligence, and work motivation are significantly positively correlated with work commitment. However, only hierarchy and market organizational culture were found to moderate the relationship between work motivation and work commitment. General and adhocracy organizational culture negatively moderated the relationship between emotional intelligence and work commitment. Additionally, significant differences in work motivation and emotional intelligence were found on demographic variable such as qualification. The findings contribute towards an enhanced understanding of a unifying model for work commitment in relation with the other variables. Higher education commission, university authorities and government in Pakistan should capitalize on organizational culture to improve emotional intelligence and work motivation among academic staff which eventually will boast their work commitment.